Cerebellopontine Angle Epidermoids: Comparative Results of Microscopic and Endoscopic Excision Using the Retromastoid Approach” - Singh, Suyash; Das, Kuntal Kanti; Kumar, Krishna; Rangari, Kamlesh; Dikshit, Priyadarshi; Bhaisora, Kamlesh Singh; Sardhara, Jayesh; Mehrotra, Anant; Srivastava, Arun Kumar; Jaiswal, Awadhesh Kumar; Behari, Sanjay (Journal of Neurological Surgery Part B: Skull Base, 2021)
Background Densely packed neurovascular structures, often times inseparable capsular adhesions and sometimes a multicompartmental tumor extension, make surgical excision of cerebellopontine angle epidermoids (CPEs) a challenging task. A simultaneous or an exclusive endoscopic visualization has added a new dimension to the classical microscopic approaches to these tumors recently.Methods Eighty-six patients (age: 31.6 ± 11.7 years, M:F = 1:1) were included. Nineteen patients (22.1%) had a multicompartmental tumor. Tumor extension was classified into five subtypes. Sixty-two patients underwent a pure microscopic approach (72%) out of which 10 patients (16%) underwent an endoscope-assisted surgery (11.6%) and 24 patients (28%) underwent an endoscope-controlled excision. Surgical outcomes were retrospectively analyzed.Results Headache (53.4%), hearing loss (46.5%), and trigeminal neuralgia (41.8%) were the leading symptoms. Interestingly, 21% of the patients had at least one preexisting cranial nerve deficit. Endoscopic assistance helped in removing an unseen tumor lobule in 3 of 10 patients (30%). Pure endoscopic approach significantly reduced the hospital stay from 9.2 to 7.3 days (p = 0.012), and had a statistically insignificant yet a clearly noticeable lesser incidence of subtotal tumor excision (0 vs. 10%, p = 0.18) with comparable cranial nerve deficits but with a higher postoperative cerebrospinal fluid (CSF) leak rate (29% vs. 4.8%, p = 0.004).Conclusion Endoscope assistance in CPE surgery is a useful addition to conventional microscopic retromastoid approach. Pure endoscopic excision in CPE is feasible, associated with a lesser duration of hospital stay, better extent of excision in selected cases, and it has a comparable cranial nerve morbidity profile albeit with a higher rate of CSF leak.
Keywords: cerebellopontine angle; epidermoid; endoscopy; multicompartmental; cisterns; classification; microsurgery; complications